A lifeline for Small Business in South Africa: An evaluation of section 12J, Venture Capital Incentives - Mynhardt, Tertius Mader (Department of Finance and Tax, 2021)
This dissertation seeks to answer two questions. In the main it aims to answer does the section 12J venture capital incentive advance government's original stated intention of incentivizing the provision of equity funds to the SME sector. Based on the outcome of the primary research question the secondary question seeks to answer whether section 12J should be extended beyond 2021. In seeking to answer these questions the dissertation critically evaluates the section 12J legislation, researches the venture capital industry in South Africa including section 12J venture capital companies and investigates the role and success of targeted tax incentives in South Africa. The VCC incentive targeted start-ups and SME's generally considered high growth and high-tech, or junior mining and exploration companies. SME's, especially entrepreneurial businesses, have the potential to be a catalyst for economic growth and job creation. Inter alia, access to finance is stunting the development of the SME sector with up to 70% of SME's failing due to a lack of funding. Venture capitalists can provide equity finance, management and technical support that could reduce some of the high risks associated with SME's. The advantage of equity finance is that it allows the SME's to better weather economic downturns and reinvest cash surpluses instead of servicing debt. In the main, whether the section 12J tax incentive is successfully advancing government's original intention still remains to be seen. Although there has been significant uptake of the regime and evidence to suggest that jobs are being created and meaningful investments are occurring, it still needs to be assessed to what extent the jobs and investments would have occurred even without the incentive. There also remain some short-comings to the design of the incentive and uncertainty to the regime which affects the sustainability of VCC's and the type of investments being made. The VCC industry has evolved to be more conservative, investing into asset-backed businesses and generally providing more growth capital, meaning that start-ups and other industries such as high growth technological companies are benefitting to a lesser extent. As such, government's intention to provide equity finance to start-ups and high growth industries appears to not be being addressed. Due to the late uptake of the regime, it is further unlikely that sufficient data would be available to analyze the incentive before 30 June 2021, the current sunset date. For these reasons, it is the writer's view that Treasury should appoint an external research organisation to prepare a thorough analysis of the incentive and whether it should be extended, but in any event, as a minimum the incentive should be extended for at least another six years (to make up for the years from its introduction to the year it began to show significant uptake, i.e. 2009 to 2015). Alternatively, the section 12J incentive should not be extended but rather replaced with a similar incentive taking into account the recommendations made in this dissertation.